Using Subcritical Water to Obtain Polyphenol-Rich Extracts with Antimicrobial Properties - Tjaša Žagar; Rok Frlan; Nina Kočevar Glavač (Antibiotics, 2024)
The use of green extraction methods that meet the criteria of sustainable and environmentally friendly technologies has been increasing in recent decades due to their many benefits. In this respect, extracts obtained using subcritical water are also gaining increased attention because of their potential antioxidant and antimicrobial properties. Their antimicrobial activity is mainly due to the presence of various polyphenolic compounds. Although the exact mechanism of the antibacterial action of polyphenolic compounds has not yet been fully investigated and described, polyphenols are known to affect the bacterial cell at several cellular levels; among other things, they cause changes and ruptures in the cell membranes of the bacterial cell, affect the inactivation of bacterial enzymes and damage bacterial DNA. The difference in the strength of the antimicrobial activity of the extracts is most likely a result of differences in their lipophilicity and in the number and position of hydroxyl groups and double bonds in the chemical structure of polyphenols. By changing the extraction conditions, especially the temperature, during subcritical water extraction, we affect the solubility of the compounds we want to extract. In general, as the temperature increases, the solubility of polyphenolic compounds also increases, and the reduction of the surface tension of subcritical water at higher temperatures also enables faster dissolution of polyphenolic compounds. Different bacterial strains have different sensitivity to different extracts. However, extracts obtained with subcritical water extraction demonstrate strong antimicrobial activity compared to extracts obtained with conventional methods.